PENGARUH KOMPETENSI, KEPUASAN KERJA, DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. BATIK SOLO TRANS SURAKARTA - Nabil Adli Multazim; M. Farid Wajdi (Jurnal Manajemen Dirgantara, 2024)
The purpose of this study was to analyze the effect of competence, job satisfaction, and work experience on the performance of employees of PT Batik Solo Trans Surakarta. This research method is quantitative. The population in this study were all drivers at PT Batik Solo Trans Surakarta, totaling 138 people. The sample used in this study were all drivers of PT Batik Solo Trans Surakarta totaling 138 people. The sampling technique in this study used saturated sampling or total sampling. The data analysis technique in this study used computer aids with the SPSS for Windows 17.0 program. The results of this study are that competence has a positive and significant effect on the performance of employees of PT BST Surakarta. Job satisfaction has a positive and significant effect on the performance of employees of PT BST Surakarta. Work experience has a positive and significant effect on the performance of employees of PT BST Surakarta. Competence, job satisfaction, and work experience together have a significant effect on the performance of employees of PT. BST Surakarta.